2023
DOI: 10.3390/toxics11020193
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Heavy Metals in Grapevine Soil and Leaf Samples in Response to Seasonal Change and Farming Practice in the Cape Winelands

Abstract: Heavy metal toxicity is a major threat to the health of both humans and ecosystems. Toxic levels of heavy metals in food crops, such as grapes, can have devastating effects on plant health and the market value of the produce. Two important factors that may influence the prevalence of heavy metals in grapevines are seasonal change and farming practices. The objectives of this study were (i) to conduct a detailed pioneer screening of heavy metal levels in soils and grapevine leaf tissues in selected wine farms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In this study, the conventional method had higher Zn, Cu, Cr, and Pb concentrations compared to the organic method, with few exception (Fuego durum wheat) [26]. A comparable report has been published [27] with more pronounced effect of conventional farming to the organic method in the cultivation soil. In contrast, higher content of Cd, Cu, Zn, Pb, Cr, and As have been reported under organic compared to conventional farming [12].…”
Section: Analysis Of Heavy Metals In Soil Samplessupporting
confidence: 70%
“…In this study, the conventional method had higher Zn, Cu, Cr, and Pb concentrations compared to the organic method, with few exception (Fuego durum wheat) [26]. A comparable report has been published [27] with more pronounced effect of conventional farming to the organic method in the cultivation soil. In contrast, higher content of Cd, Cu, Zn, Pb, Cr, and As have been reported under organic compared to conventional farming [12].…”
Section: Analysis Of Heavy Metals In Soil Samplessupporting
confidence: 70%
“…At the same time, some papers showed that concentrations of copper in the organic vineyards were higher than in the conventional vineyards of the studies. Ecological indices corresponding to moderate-to-heavy contamination and moderate ecological risk in organic farms were higher than ones in conventional farms [14].…”
Section: Introductionmentioning
confidence: 73%
“…This issue has become a global concern [3,4]. It has been identified as the third most significant threat to soil functions in Europe and Eurasia, fourth in North Africa, fifth in Asia, seventh in the Northwest Pacific, eighth in North America, and ninth in sub-Saharan Africa and Latin America [1].…”
Section: Introductionmentioning
confidence: 99%